PENDATAAN HASIL PRODUKSI PISANG BERBASIS KERUANGAN DI KABUPATEN LUMAJANG - Dwi Putro Sarwo Setyohadi; Hendra Yufit Riskiawan (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Bananas are one of the largest fruit commodities produced by farmland Lumajang compared with other fruit commodities. The amount of the production of bananas produced by Lumajang need to do a better collection of any amount of bananas each districts. Geographic Information Systems (GIS) or information systems development based spatial is information system capable of providing spatial information (spatial reference) in which the information generated can be viewed along with the map pointer location. Geographic Information Systems (GIS) Data Collection Banana Production in Lumajang used to assist in the collection of existing banana production earlier can also help related agencies namely the Department of Agriculture Lumajang in providing spatial reference information, especially the production of bananas. Data Collection Banana Production in Lumajang with this system can display information such as the amount of production per type of bananas produced by each of the districts in Lumajang and graph the results of banana production to inform the development of the production of bananas per year.